Financial Literacy, Lifestyle, and Employees' Financial Behavior - Al Qorni, Hawa; Widiyanti, Dwi Retno (Contemporary Studies in Economic, Finance and Banking, 2026)
The low level of financial literacy in Indonesia remains an important issue because it can affect how individuals manage income, control consumption, prepare savings, and make financial decisions. This study aims to examine the influence of financial literacy and lifestyle on the financial behavior of employees in Gresik Regency. This research uses a quantitative approach with employees in Gresik Regency as the research object. The data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software. The results show that financial literacy has a significant influence on financial behavior, as indicated by a significance value of 0.000 < 0.05. This means that employees with better financial literacy tend to demonstrate better financial management behavior. Meanwhile, lifestyle does not have a significant influence on financial behavior, as shown by a significance value of 0.313 > 0.05. These findings imply that improving financial literacy is more essential than lifestyle factors in strengthening employees’ financial behavior, especially in supporting better budgeting, saving habits, and financial decision-making